New approach for 6 cylinder diesel electric algorithm control on one cylinder failure - Shifte, Changiz; Abedini, Hossein; Akbarifard, Abdolmajid; Ebrahim Afjei, S. (2015 6th Power Electronics, Drives Systems and Technologies Conference (PEDSTC), 2015)
Because of nonresistance loading, stability of local network electricity frequency is very important in the alternative electricity generator. Since load consumer equipment would be damaged if the frequency is not in the allowable range, so the frequency fluctuation must be as low as it is possible. Non fluctuated frequency of diesel-electric alternator dependents on the diesel engine speed stability, so keeping the speed in stability range is very important. There is a 6 cylinder diesel-electric that work in part load and a failure takes place suddenly in one of the cylinders. So a new approach control algorithm is presented for keeping engine speed in the allowable range.